Novel Geobacillus thermoleovorans KNG 112 Thermophilic Bacteria from Bandaru Hot Spring: A Potential Producer of Thermostable enzymes. - KR, KOTRESH; NEELAGUND, SHIVAYOGEESWAR; DM, GURUMURTHY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Amylase and lipase producing novel bacterium (strain IC5) were isolated from Bandaru hot spring, Karnataka, India. The cell was found to be thermophilic, gram-positive, aerobic, non-motile, capable of growing at different optimum parameters of pH 7, temperature 55°C and tolerated maximally 0-8% (w/v) NaCl, which has the ability to show good amylotic and lipolytic activities. Phylogenetic analysis of the bacterium using the 16S rRNA gene was revealed that the strain belongs to genus Geobacillus. The isolated strain IC5 was in close resemblance with the gene of Geobacillus thermoleovorans EC-5 having 99% of similarities. During the production of amylase, the maximum activity was found when temperature and pH ranged from 50 to 60 ºC and from 7 to 8 respectively. The strain used starch as a carbon source with an agitation speed of 120rpm for maximal amylase production.